Green development growth momentum under carbon neutrality scenario - Wan, Bingyue; Tian, Lixin; Fu, Min; Zhang, Guangyong (Journal of cleaner production, 2021)
With the general recognition of the awareness of carbon neutrality, economic development growth momentum for carbon neutrality scenario has become research focus. This paper introduces the carbon neutrality double input level based on the perspective of the initiative, consciousness, and self-discipline of firms and residents to practice green low-carbon behavior. By constructing a balanced economic system of green low-carbon behavior, this paper explores the new endogenous growth power in production and consumption, and finds that there exists a carbon neutrality realization regulation of green low-carbon behavior in the new system. Based on the penetration capacity of green low-carbon behavior, this paper studies the endogenous growth law of economic system driven by the evolution of carbon neutrality double input level. The production and consumption processes are considered in the new economic system in this paper, the production of green low-carbon goods is considered in the production sector and the technical equation under carbon neutrality double input level is studied, the consumption process of green goods affected by environment and carbon emissions is considered in the household, then the household utility function is constructed, and the new growth rate is obtained. Using carbon emissions growth rate of green low-carbon goods and its relationship with absorption rate derive the carbon neutrality realization regulation. Then the general equilibrium solution and growth rate under endogenous growth driven by carbon neutrality double input level are also obtained. Furthermore, the carbon neutrality effects which are the endogenous effect of carbon neutrality double input level and the effect of carbon neutrality realization regulation are obtained by numerical simulation and empirical analysis.